2014
DOI: 10.1002/jrs.4606
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation with Raman spectroscopy among several natural ultramarine blues and the synthetic ultramarine blue used by the Catalonian modernist painter Ramon Casas i Carbó

Abstract: This paper investigates, using only Raman spectroscopy, the spectral differences among the synthetic ultramarine blue (J. B. Guimet) and three natural ultramarine blues (lazurites) corresponding to three lapis lazulis from different geographical sources (Chile, Afghanistan and Siberia). The synthetic ultramarine blue used as reference pigment is the identified in an artwork created around 1917 by the Catalonian modernist painter Ramon Casas i Carbó. This synthetic pigment is compared with the three natural ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…These features may be indicative of natural lapis lazuli from Afghanistan. De Torres et al tried to quantify the Raman spectral differences up to about 2000 cm −1 amongst the synthetic ultramarine blue and three lazurites corresponding to three lapis lazulis from different geographical sources (Chile, Afghanistan, Siberia).…”
Section: Introductionmentioning
confidence: 99%
“…These features may be indicative of natural lapis lazuli from Afghanistan. De Torres et al tried to quantify the Raman spectral differences up to about 2000 cm −1 amongst the synthetic ultramarine blue and three lazurites corresponding to three lapis lazulis from different geographical sources (Chile, Afghanistan, Siberia).…”
Section: Introductionmentioning
confidence: 99%
“…De Torres and co‐workers describe the Raman differentiation of several natural ultramarine blues and the synthetic ultramarine blue used by the Catalonian modernist painter Ramon Casas i Carbo. This synthetic pigment is compared with the three natural ultramarine blues and, in his turn, the latter are also compared each other . Dominguez‐Vidal and co‐workers carried out a comparative field and laboratory Raman study of decorated plasterwork in the Alhambra Field investigations were carried out in‐situ using a portable Raman spectrometer during a conservation campaign in a completely non‐invasive manner.…”
Section: Art and Archeologymentioning
confidence: 99%
“…The Raman spectral differences among the synthetic ultramarine blue (from the J. B. Guimet manufacturer) and three natural ultramarine blues (lazurites from different geographical sources: Chile, Afghanistan and Siberia) have been investigated by De Torres et al [45] The synthetic ultramarine blue used as reference pigment was identified in an artwork created around 1917 by the Catalonian modernist painter Ramon Casas i Carbo. The comparison of this synthetic pigment with the three natural lapis lazuli was performed using a home-made rigorous methodology based on the Euclidean distance between homologue spectral segments (or intervals).…”
Section: New Raman Instrumentation and Applicationsmentioning
confidence: 99%
“…The Raman spectral differences among the synthetic ultramarine blue (from the J. B. Guimet manufacturer) and three natural ultramarine blues (lazurites from different geographical sources: Chile, Afghanistan and Siberia) have been investigated by De Torres et al . The synthetic ultramarine blue used as reference pigment was identified in an artwork created around 1917 by the Catalonian modernist painter Ramon Casas i Carbo.…”
Section: New Raman Instrumentation and Applicationsmentioning
confidence: 99%